The role of perceived religiosity in strengthening celebrity endorser's credibility dimensions - Sahat Aditua Fandhitya Silalahi; Fachrurazi Fachrurazi; Achmad Muchaddam Fahham (Cogent Business & Management, 2021)
This present study investigates the moderating effect of celebrity endorsers' perceived religiosity in the relationship between dimensions in source credibility theory and consumers' purchase intention. A self-administered survey was conducted using mock-up stimuli to 505 respondents in major universities located in Jakarta, Indonesia. Subsequently, exploratory and confirmatory factor analysis was employed, followed by regression analysis using AMOS 24.0 to test the hypotheses. The results revealed that endorsers' perceived religiosity significantly strengthened the influences of trustworthiness and attractiveness dimensions toward consumers' purchase intention. Conversely, perceived religiosity did not significantly strengthen the effect of expertise on consumers' purchase intention. Theoretically, this present study fulfills the knowledge gap of the influence of perceived religiosity construct on the relationship between source credibility dimensions and consumers' purchase intention. While practically, this present study provides suggestions for marketers to involve the celebrity's perceived religiosity dimensions to increase their endorsement campaigns' credibility and effectiveness.
Keywords: 650; Source credibility theory; perceived religiosity; celebrity endorsement; trustworthiness; expertise; attractiveness